Uma análise feminista acerca do contrato de casamento e da obrigação de caráter sexual dele decorrente - Alves, Clarissa Cecília Ferreira (2012)
The current dissertation proposes to investigate the positioning of the Brazilian right concerning the existence of an obligation of sexual character decurrent from the marriage contract, in the intention to evaluate if this, while main agreement that creates the family in the patriarchal molds, has been, since the beginning of contractual theorization, conceived having as presupposition the feminine subordination to the masculine domain, as if this resulted from a natural and universal order. Leaving from a feminist point of view, specially from the current known as Radical Feminism, it will be searched to analyze the marriage in its contractual manifestation, having as presumption the sexual contract theory of Carole Pateman and her thesis that there is a male sexual right of systematic access to the body of women, of which the sexual obligation derives directly. Initially, it will be presented the discussion about the separation proposed by the liberal theory between public and private, considering how much the inequality presented in the private sphere has been ignored throughout history and, therefore, socially legitimated. Later, it will be made a critical analysis about the liberal fiction of social contract, from the modern conception of patriarchy. Next, it will be undertaken the investigation itself about the reception of the obligation of sexual character (or conjugal debit) in the Brazilian doctrine and jurisprudence. Finally, it will be taken into account that, although it s possible to glimpse a legal evolution in the sense of formally treating men and women as equals, the Brazilian legal system shows to be conservative and sexist when dignifying the marriage as the main form of family constitution and when serving as support to the male sexual right of systematic access to the body of women.